Landscape Architecture Framed from an Environmental and Ecological Perspective - Ergen, Mustafa; Bahri Ergen, Yaşar (IntechOpen, 2022)
Landscape architecture involves designing, planning, and managing natural and built environments. Its goal is to balance natural spaces with the human element. As such, new methods and analysis techniques are necessary for creating healthy and user-friendly spaces in both urban developments and natural environments. This book discusses these approaches to planning and designing natural spaces with a focus on sustainability.